9v=7v+6

Simple and best practice solution for 9v=7v+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9v=7v+6 equation:


Simplifying
9v = 7v + 6

Reorder the terms:
9v = 6 + 7v

Solving
9v = 6 + 7v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-7v' to each side of the equation.
9v + -7v = 6 + 7v + -7v

Combine like terms: 9v + -7v = 2v
2v = 6 + 7v + -7v

Combine like terms: 7v + -7v = 0
2v = 6 + 0
2v = 6

Divide each side by '2'.
v = 3

Simplifying
v = 3

See similar equations:

| 3/8+5/12=8/20 | | 8*63+8*3= | | f(20)=2(20)-18 | | x=14-y | | 5x+22=441 | | -85=8x-13 | | 9v+4b=219 | | 5(2t+5)=35 | | w/3-3w | | 9-2y=35 | | f(x)=2x-18 | | -3(w-4)=9w-36 | | 58/18 | | x+15=4x-19 | | -4k+3.2=7.8 | | 7x+14y=784 | | 16-3j=10 | | -4+b=11 | | 3-1=4x-5 | | 2x+14+x+26=2x+60 | | y=2x+(3x-2)-5 | | Y=15+5 | | 35x=20+25x | | 11b+11v=451 | | 8-(x-4)2= | | 4(x+5)=3(x+4) | | N*57=45 | | 6d-4+4=2d+14 | | -6p-7+2p-3-4p= | | 1/8+1/8=1/16 | | X+(x+2)+(x+3)=x(x+2)-36 | | y+10.2=13 |

Equations solver categories